EXAMINING THE IMPACT OF ILLOCUTIONARY ACTS ON STUDENT ENGAGEMENT: A MIXED-METHODS STUDY - Wardhana, I Gede Neil Prajamukti; Dewi, Ni Luh Desy Suari; Nainggolan, Fidelio Juan Gawi (STKIP Persada Khatulistiwa Sintang, 2024)
This study used qualitative and quantitative methods to analyze the impact of speech acts, particularly illocutionary acts, on student engagement at Wira Harapan High School. Illocutionary acts, or expressions that perform actions (Vanderveken, 1990), are crucial for teacher-student communication. Through classroom observations and teacher interviews, this research examines their role in daily teaching. Over the course of the course of three months, diverse classes were observed to categorize instances of illocutionary acts. Interviews with teachers provided insights into their intentional use. Qualitative analysis and quantitative assessment offer a comprehensive understanding of their effect on student engagement. This study used the illocutionary acts theory (Searle, 1969) to underscore the importance of mindful communication in transforming the educational experience at Wira Harapan High School.Keywords: Illocutionary Acts, Wira Harapan High School, Speech Acts.